Flexibilidade na organização do trabalho em sistemas de produção de leite no Norte do Paraná - Brasil e no Departamento de La Loire - França - Santos Filho, Joel Carneiro dos (2012)
The aim, of this thesis was to characterize and analyze the flexibility work organization in dairy production systems (DPS). The study was performed in 20 DPS in northern Paraná - Brazil and 10 DPS in the department of La Loire - France. The flexibility that had been studied in Brazil relates to the room for manoeuvre in time, while in France was studied in addition to the room for manoeuvre in time, the adaptive capabilities of systems. Semi-structured interviews were conducted with the farmer and/or his family. The QuaeWork method (QUAlification and Evaluation of Work in livestock farms) was used to characterize the shape and duration of the work. For the construction of the variables, it was used repertory grid method and for the definition of farmers groups, it was used the graphical method of Bertin, adapted to small samples. The results related to room for manoeuvre in time, quantified in hours per year available, were variable in both regions: (i) in northern Paraná, the room for manoeuvre in time per farmer had an average of 732 hours/year, with standard deviation of 493 hours/year; (ii) for the department of La Loire, the room for manoeuvre in time per farmer had an average of 987 hours/year, with standard deviation of 316 hours/year. With respect to typology, in northern Paraná four types of MSP were identified. It varied between a producer work alone and with simpler equipment for the transport of forages (cart), having a low room for manoeuvre in time (<600 hours/year) and other producer who has employed or volunteer help and has better transport equipment forage (wagon), he has more room for manoeuvre in time (>1000 hours/year) and also has high capacity to adapt to events. For its part, the department of La Loire was obtained five types of MSP, with different combinations of the room for manoeuvre in time and adaptive capacities. There is the type with low room for manoeuvre in time, but with great capacity to adapt to events, but there is also the type that has high. One type has great flexibility in work organization, that is linked to both high room for manoeuvre in time (>1000 hours/year), and by the capacities that the DPS has to adapt to events. In both regions, the flexibility was explained by the different forms in the use of manpower, machinery and equipment and management adopted by the DPS. Conclude that it is possible to know the situation of the DPS with respect to flexibility in work organization, and from this knowledge, can be proposed adjustments aiming to improve the systems, making them sustainable and with the possibility of its reproduction.